2013
DOI: 10.1002/mrm.24885
|View full text |Cite
|
Sign up to set email alerts
|

Influence of eddy current, Maxwell and gradient field corrections on 3D flow visualization of 3D CINE PC-MRI data

Abstract: Purpose The measurement of velocities based on PC-MRI can be subject to different phase offset errors which can affect the accuracy of velocity data. The purpose of this study was to determine the impact of these inaccuracies and to evaluate different correction strategies on 3D visualization. Methods PC-MRI was performed on a 3 T system (Siemens Trio) for in vitro (curved/straight tube models; venc: 0.3 m/s) and in vivo (aorta/intracranial vasculature; venc: 1.5/0.4 m/s) data. For comparison of the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 23 publications
2
63
0
Order By: Relevance
“…While other studies have investigated background‐phase offsets in 4D‐flow MRI, this is the first study to provide a comprehensive analysis of the influence of different correction techniques on vascular flow‐volume measurements. Lorenz et al performed a streamline and pathline tracking analysis that showed improvement with second order, compared with linear background phase fitting in phantom experiments, but no discernable difference in in vivo tracking, agreeing with our results . Ebbers et al demonstrated that higher‐order fitting results in improved velocity correction in static tissue, as we have also shown .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While other studies have investigated background‐phase offsets in 4D‐flow MRI, this is the first study to provide a comprehensive analysis of the influence of different correction techniques on vascular flow‐volume measurements. Lorenz et al performed a streamline and pathline tracking analysis that showed improvement with second order, compared with linear background phase fitting in phantom experiments, but no discernable difference in in vivo tracking, agreeing with our results . Ebbers et al demonstrated that higher‐order fitting results in improved velocity correction in static tissue, as we have also shown .…”
Section: Discussionsupporting
confidence: 91%
“…Background phase correction of 4D‐flow data has been demonstrated to be important for obtaining accurate pathline and streamline traces for flow visualization . More recently, Busch et al used an image‐based assessment of 4D‐flow MRI background phase‐correction sensitivity to polynomial fit order and static tissue .…”
Section: Introductionmentioning
confidence: 99%
“…Gradient non‐linearities are caused by geometric limitations in the gradient coils, which result in unwanted higher order, nonlinear encoding gradients . Concomitant gradients are nonlinear, spatially dependent magnetic fields that are generated when a linear magnetic field gradient is activated . Gradient nonlinearities and concomitant gradients both cause phase errors but can be corrected for and eliminated during image reconstruction without user intervention .…”
Section: Introductionmentioning
confidence: 99%
“…Eddy currents are created from rapidly switching the velocity encoding gradient during acquisition. This switching causes a change in the magnetic flux at the gradient coils, leading to spatially varying phase errors on the image . The magnitude of these eddy currents are based on the flow velocity at the ROI, as regions with slow flow require stronger encoding gradients resulting in larger field distortions .…”
Section: Introductionmentioning
confidence: 99%
“…All data were corrected for Maxwell terms during reconstruction, and for eddy currents and velocity noise using a specialized in‐house tool (MATLAB, MathWorks, Natick, MA). In vitro, background phase was corrected by subtracting the image collected under identical conditions but with flow turned off . As shown in Fig.…”
Section: Methodsmentioning
confidence: 99%